2006
DOI: 10.1038/sj.bjp.0706745
|View full text |Cite
|
Sign up to set email alerts
|

The PPARα/γ dual agonist chiglitazar improves insulin resistance and dyslipidemia in MSG obese rats

Abstract: 1 The aim of this study was to investigate the capacity of chiglitazar to improve insulin resistance and dyslipidemia in monosodium L-glutamate (MSG) obese rats and to determine whether its lipidlowering effect is mediated through its activation of PPARa. 2 Chiglitazar is a PPARa/g dual agonist.3 The compound improved impaired insulin and glucose tolerance; decreased plasma insulin level and increased the insulin sensitivity index and decreased HOMA index. Euglycemic hyperinsulinemic clamp studies showed chigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 35 publications
(40 reference statements)
1
41
0
2
Order By: Relevance
“…Chiglitazar (33), a PPAR / agonist, by suppressing the expression of genes for the key gluconeogenic enzymes PEPCK and G-6-Pase and upregulating mRNA expression of genes involved in NEFA oxidation, demonstrated to reduce insulin resistance and to improve glucose tolerance and lipid profiles in monosodium L-glutamate obese rats [273]. Unfortunately, this study does not report data on liver fibrosis.…”
Section: Dual or Pan Ppars Agonistsmentioning
confidence: 58%
“…Chiglitazar (33), a PPAR / agonist, by suppressing the expression of genes for the key gluconeogenic enzymes PEPCK and G-6-Pase and upregulating mRNA expression of genes involved in NEFA oxidation, demonstrated to reduce insulin resistance and to improve glucose tolerance and lipid profiles in monosodium L-glutamate obese rats [273]. Unfortunately, this study does not report data on liver fibrosis.…”
Section: Dual or Pan Ppars Agonistsmentioning
confidence: 58%
“…Studies have shown that successful beta cell adaptation to insulin resistance includes increasing beta cell mass via hypertrophy and/or hyperplasia [30]. However, few studies have been conducted to evaluate the endocrine characteristics of the pancreas in MSG-treated obese rats, and the data that have been reported are contradictory [22,31]. The proliferation of pancreatic islets is modulated by parasympathetic vagal activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…This could perhaps be indicative of onset of hepatic insulin resistance, as reported in a previous study (35), which has yet to affect whole body insulin resistance or glucose tolerance. Although the use of HOMA as a measurement of insulin resistance in rodent studies is quite common (14,27), it is also controversial (38) and better suited to larger cohorts. Nevertheless, our finding of elevated HOMA in the Restricted female rats suggests that alterations in insulin sensitivity could be occurring in our model of restriction that might be more readily detected by more sensitive measures such as a euglycemic hyperinsulinemic clamp.…”
Section: Discussionmentioning
confidence: 99%